GCN2 Deficiency Enhances Protective Effects of Exercise on Hepatic Steatosis. (24th November 2020) - Luo, Xueting; Shi, Xiaowei; Sun, Zhongguang; Xiao, Jing; Song, Hui; Lu, Guo; Xu, Xin
Abstract : Background . Combined aerobic and resistance training has been demonstrated to benefit glycemic control and reverse nonalcoholic fatty liver disease in childhood obesity. General control nonderepressible 2 (GCN2) deficiency has been reported to attenuate hepatic steatosis and insulin resistance. However, whether GCN2 impacts the positive effects of combined aerobic and resistance exercise remains unknown. Objectives . To investigate whether combined aerobic and resistance exercise improves hepatic steatosis and glucose intolerance and the role GCN2 plays in mediating the metabolic regulation of exercise. Methods . Wild-type (WT) and GCN2 knockout (GCN2KO) mice were fed a high-fat diet (HFD) for 25 weeks. The WT and GCN2KO mice performed exercise (treadmill running + ladder climbing) during the last eight weeks. Their body and liver weights, their triglyceride content, and their levels of aspartate transaminase (AST), alanine transaminase (ALT), and blood glucose were measured, and the expressions of proteins involved in the GCN2/eIF2 α /ATF4 pathway and the glucolipid metabolism-related proteins (e.g., p-AMPK, SIRT1, PPAR α, PGC-1 α, GLUT4, and p-GSK-3 β ) were determined. Results . The body weight of WT and GCN2KO mice continued to increase until the end of the experiment. The liver weights, hepatic triglyceride content, and AST and ALT levels of the exercised mice were significantly reduced compared to those of the sedentary mice. Exercise improved blood glucose levels and glucose clearance ability in the WT mice, but the glucose intolerance of GCN2KO mice was not improved. Exercise increased PGC-1 α, GLUT4, and p-GSK-3 β expressions in the WT rather than the GCN2KO mice. Interestingly however, exercise-trained GCN2KO mice were better protected against hepatic steatosis with downregulated expressions of p-eIF2 α and ATF4, upregulated expressions of p-AMPK and SIRT1, and the presence of PPAR α in the liver, compared to the exercised WT mice. Conclusion . Combined aerobic and resistance exercise had positive effects on hepatic steatosis and the control of glucose intolerance. GCN2 was found to be necessary for exercise-induced improved glucose intolerance. However, the better efficacy in improving hepatic steatosis by exercise in the GCN2 -deficient mice enhanced liver lipid metabolism, at least partially, via the AMPK/SIRT1/PPAR α pathway.